Las fronteras de los residuos: tres movimientos para comprender la actualidad de los cartoneros en la ciudad de Buenos Aires - Tagliafico, Juan Pablo (2022)
This article aims to address the changing relationship between waste and urban space in Buenos Aires. Specifically, based on an analysis of the period between 1976 and 2019, it seeks to understand the way in which cartoneros (waste pickers) are inscribed today. By studying the productive role played by frontiers as sites of conflict, this paper presents three movements in which borders trace over waste. This mapping reveals the place of the cartoneros as important actors in a network that links waste management, the production of urban space, and a certain way of organizing the labor force.